THE INFLUENCE OF FORMAL COMMUNICATION IN THE PROCESS OF ACCESSING EUROPEAN FUNDS - Zait, Luminita (Studies and Scientific Researches. Economics Edition, 2014)
Present article aims, based on direct research, to identify of main sources of information in the process of accessing European funds. Performed within Trotus Valley, Bacau, the proposed research provides pertinent information from the perspective of the main sources of influence on the manifestation of interest in accessing funding and in terms of highlighting the influence of various socio-demographic variables on such information sources. According to the Romanian experience of accessing European funds, apparently formal communication efforts prove ineffective, being less reliable and stimulating compared to the informal interpersonal communication. Because most of the potential beneficiaries of EU funds precept this process as one dominated by sinuous and powerful bureaucracy, we tend to believe that in the expressions of interest in accessing EU funds, formal communication only meet the cognitive structure of attitude, affective and conative entering under the influence of informal communication.